Development and evaluation of in vivo tissue engineered blood vessels in a porcine model. (January 2016) - Rothuizen, Tonia C.; Damanik, Febriyani F.R.; Lavrijsen, Tom; Visser, Michel J.T.; Hamming, Jaap F.; Lalai, Reshma A.; Duijs, Jacques M.G.J.; van Zonneveld, Anton Jan; Hoefer, Imo E.; van Blitterswijk, Clemens A.; Rabelink, T.J.; Moroni, Lorenzo; et al.
Abstract: Background: There's a large clinical need for novel vascular grafts. Tissue engineered blood vessels (TEBVs) have great potential to improve the outcome of vascular grafting procedures. Here, we present a novel approach to generate autologous TEBV in vivo . Polymer rods were engineered and implanted, evoking an inflammatory response that culminates in encapsulation by a fibrocellular capsule. We hypothesized that, after extrusion of the rod, the fibrocellular capsule differentiates into an adequate vascular conduit once grafted into the vasculature. Methods and results: Rods were implanted subcutaneously in pigs. After 4 weeks, rods with tissue capsules grown around it were harvested. Tissue capsules were grafted bilaterally as carotid artery interposition. One and 4-week patency were evaluated by angiography whereupon pigs were sacrificed. Tissue capsules before and after grafting were evaluated on tissue remodeling using immunohistochemistry, RNA profiling and mechanical testing. Rods were encapsulated by thick, well-vascularized tissue capsules, composed of circumferentially aligned fibroblasts, collagen and few leukocytes, with adequate mechanical strength. Patency was 100% after 1 week and 87.5% after 4 weeks. After grafting, tissue capsules remodeled towards a vascular phenotype. Gene profiles of TEBVs gained more similarity with carotid artery. Wall thickness and αSMA-positive area significantly increased. Interestingly, a substantial portion of (myo)fibroblasts present before grafting expressed smooth muscle cell markers. While leukocytes were hardly present anymore, the lumen was largely covered with endothelial cells. Burst pressure remained stable after grafting. Conclusions: Autologous TEBVs were created in vivo with sufficient mechanical strength enabling vascular grafting. Grafts differentiated towards a vascular phenotype upon grafting.